Edible Alginate–Fungal Chitosan Coatings as Carriers for Lacticaseibacillus casei LC03 and Their Impact on Quality Parameters of Strawberries During Cold Storage - Camila Vilela da Silva Simões; Thayza Christina Montenegro Stamford; Lúcia Raquel Ramos Berger; Alessandra Silva Araújo; José Alberto da Costa Medeiros; Mariane Cajubá de Britto Lira Nogueira; Maria Manuela Estevez Pintado; Silvana Magalhães Salgado; Marcos Antonio Barbosa de Lima (Foods)
This study investigated the efficacy of an innovative edible coating, composed of fungal chitosan and alginate, functionalized with Lacticaseibacillus casei LC03, in both free and microencapsulated forms, to extend the shelf life and enhance the nutritional value of strawberries. L. casei LC03 cells were successfully encapsulated in alginate microparticles (MAL) and further coated with chitosan (MALC), resulting in enhanced protection (cell reduction below 1.4 CFU/mL), viability (8.02 log CFU/mL), and encapsulation efficiencies exceeding 90%. The edible coating with L. casei microencapsulated in alginate and coated with fungal chitosan (CACLM) significantly improved strawberry preservation by maintaining pH (3.16 ± 0.41), titratable acidity (0.94 ± 0.20), moisture (90.74 ± 0.27), and microbial quality, and delayed the decrease in total phenolic compounds (below 40%) during the storage time of strawberries. While coatings with free L. casei (CALF) slightly reduced color parameters (L* value 29.13 ± 2.05), those with chitosan (CACLM) demonstrated lower weight loss (below 6%). Overall, the alginate–chitosan coating, particularly when combined with microencapsulated L. casei, proved effective in maintaining the quality, safety, and nutritional value of strawberries during refrigerated storage, highlighting its potential for developing functional, eco-friendly packaging solutions. This research contributes to the development of sustainable food preservation strategies and functional foods.